Objektivitas AI dalam Rekrutmen dan Seleksi: Solusi atau Tantangan? - Pratama, Yudhistira Anugerah; Isnajati, Louisiani Mansoni; Djabbar, Husnawati (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study investigates the use of artificial intelligence (AI) in employee recruitment and selection, focusing on enhancing objectivity and fairness. Employing both quantitative and qualitative methods, the research reveals that AI can improve efficiency, transparency, and consistency by evaluating candidates based on skills, experience, and job fit. However, the study also highlights that AI is not entirely free from bias, especially when trained on data reflecting historical discrimination. Therefore, organizations must recognize AI's limitations and ensure ongoing evaluation of these systems. While AI offers great potential to reduce human bias, it requires careful implementation with human oversight. The study concludes by recommending the development of ethical algorithms and promoting digital literacy among HR decision-makers to ensure fair and inclusive recruitment practice.